Tanshinone IIA Combined With Cyclosporine A Alleviates Lung Apoptosis Induced by Renal Ischemia-Reperfusion in Obese Rats - Tai, He; Jiang, Xiao-lin; Song, Nan; Xiao, Hong-he; Li, Yue; Cheng, Mei-jia; Yin, Xiao-mei; Chen, Yi-ran; Yang, Guan-lin; Jiang, Xiao-yu; Kuang, Jin-song; Lan, Zhi-ming; et al. (Frontiers in Medicine, 2021)
Acute lung injury (ALI), which is induced by renal ischemia-reperfusion (IR), is one of the leading causes of acute renal IR-related death. Obesity raises the frequency and severity of acute kidney injury (AKI) and ALI. Tanshinone IIA (TIIA) combined with cyclosporine A (CsA) was employed to lessen the lung apoptosis led by renal IR and to evaluate whether TIIA combined with CsA could alleviate lung apoptosis by regulating mitochondrial function through the PI3K/Akt/Bad pathway in obese rats. Hematoxylin-eosin (HE) staining was used to assess the histology of the lung injury. Terminal deoxynucleotidyl transferase-mediated dUTP nick end-labeling (TUNEL) was used to assess apoptosis of the lung. Electron microscopy was used to assess mitochondrial morphology in lung cells. Arterial blood gas and pulmonary function were used to assess the external respiratory function. Mitochondrial function was used to assess the internal respiratory function and mitochondrial dynamics and biogenesis. Western blot (WB) was used to examine the PI3K/Akt/Bad pathway-related proteins. TIIA combined with CsA can alleviate lung apoptosis by regulating mitochondrial function through the PI3K/Akt/Bad pathway in obese rats.